A outra face: uma representação sobre o lazer noturno na avenida Tiradentes em Maringá, PR - Oliveira, Tânia Peres de (2017)
The main research objective was to understand how the practice of nighttime leisure is constituted, with the guiding axis being the appropriation of spaces by the subjects in Avenida Tiradentes, Zone 01, central area of Maringá city, Paraná. Initially the research was directed in order to characterize the study area identifying three distinct spaces composition, as the commercial establishments of nocturnal leisure, and two squares. Later, in order to understand the phenomenon better, it was sought to understand the conceptions about leisure, and also of its components, such as free time, play and leisure, and from there, the occurrence of leisure as an integral part subjects life, being present in the spheres of religion, family, culture and work. The phenomena that involve leisure have their occurrence from space, and this being one geographic science analysis categories, it becomes pertinent the interlocution between Geography and leisure, congregating the city as a socio-spatial relations space and still the commercial establishments and the squares like locus for the leisure. In order to gather information, were carried out observations and interviews with fifteen visitors from the different spaces that make up Avenida Tiradentes and, afterwards, were analyzed according to the methodology of "content analysis". The collected data indicate that both commercial establishments focused on night time leisure, as well as Renato Celidônio square and the Cathedral presented the consumerist leisure logic, though in different forms and intensities, also denoting disparities as regards to its forms of appropriation and interaction between the subjects, corresponding to the Cathedral Square, the space that indicates greater resistance to the capitalist logic of leisure, potentialities for diverse activities and greater social interaction .